Marinitenerispora sediminis gen. nov., sp. nov., a member of the family Nocardiopsaceae isolated from marine sediment - Ng, Zoe Yi; Fang, Bao Zhu; Li, Wen Jun; Tan, Geok Yuan Annie (Society for General Microbiology, 2019)
Three novel actinobacterial strains, designated as TPS16T, TPS81 and TPS83, were isolated from a sample of marine sediment collected from Tioman Island, Malaysia. The strains formed abundant branched substrate mycelia without fragmentation along with production of blue spores and blue diffusible pigment on soybean meal agar. The strains could grow at pH ranging from pH 6 to 12 and in 0-8% (w/v) NaCl. Cell-wall hydrolysis showed the presence of meso-diaminopimelic acid. The strains were closely related to Marinactinospora thermotolerans SCSIO 00652T (97.60 %) and Marinactinospora endophytica YIM 690053T (96.87%) based on phylogenetic analysis of 16S rRNA gene sequences. Multilocus sequence analysis including gyrB, recA and rpoB genes further confirmed that strain TPS16T represented a distinct branch within the family Nocardiopsaceae. The predominant menaquinones were MK-11(H2), MK-10(H2), MK-11(H4) and MK-10(H4), while the major fatty acids were found to be iso-C16:0, anteiso-C17:0, iso-C15:0 and C18:1ω9c. Genome sequencing revealed genome sizes of approximately 6 Mb and G+C contents of 73.8 mol%. A new genus, Marinitenerispora gen. nov., is proposed within the family Nocardiopsaceae based on polyphasic data and the type species is Marinitenerispora sediminis gen. nov., sp. nov. The type strain is TPS16T (=DSM 46825T=TBRC 5138T). © 2019 The Authors.